Novel Approach to Pharmaceutical 3D-Printing Omitting the Need for Filament-Investigation of Materials, Process, and Product Characteristics - Thomas Pflieger; Rakesh Venkatesh; Markus Dachtler; Karin Eggenreich; Stefan Laufer; Dominique Lunter (MDPI AG, 2022)
The utilized 3D printhead employs an innovative hot-melt extrusion (HME) design approach being fed by drug-loaded polymer granules and making filament strands obsolete. Oscillatory rheology is a key tool for understanding the behavior of a polymer melt in extrusion processes. In this study, small amplitude shear oscillatory (SAOS) rheology was applied to investigate formulations of model antihypertensive drug Metoprolol Succinate (MSN) in two carrier polymers for pharmaceutical three-dimensional printing (3DP). For a standardized printing process, the feeding polymers viscosity results were correlated to their printability and a better understanding of the 3DP extrudability of a pharmaceutical formulation was developed. It was found that the printing temperature is of fundamental importance, although it is limited by process parameters and the decomposition of the active pharmaceutical ingredients (API). Material characterization including differential scanning calorimetry (DSC) and thermogravimetric analyses (TGA) of the formulations were performed to evaluate component miscibility and ensure thermal durability. To assure the development of a printing process eligible for approval, all print runs were investigated for uniformity of mass and uniformity of dosage in accordance with the European Pharmacopoeia (Ph. Eur.).